C19 Track Tghd Minipigs – A Discrimination Test As Part Of An Assessment Battery For Tghd Minipigs. (17th September 2014) - Schramke, S; Schuldenzucker, V; Ott, S; Wirsig, M; Frank, F; Schubert, R; Marcegaglia, M; Hölzner, E; Reilmann, R
Abstract : Background: The TRACK tgHD minipig study aims to evaluate the potential of the Libechov tgHD minipig model for pre-clinical studies by studying the phenotype of these animals. Established tests for assessing different domains of possible phenotype manifestation in minipigs are lacking. The "Discrimination Test" introduced here is thought to primarily target cognitive dysfunction. Aim: To assess the feasibility and tolerability of the application of the "Discrimination Test" in minipigs and explore the tgHD minipigs' performance compared with that of wildtype (wt) minipigs. Methods/techniques: Thirty-two minipigs – 18 wt and 14 tg (with an N-terminal fragment of the huntingtin gene coding for 548aa with 124Q) – were included in the study. The minipigs were housed in six mixed groups (wt and tg) at the animal facility of the University of Muenster, Germany. The "Discrimination Test" was performed using a special setup. During initial training, the minipigs learnt to leave a startbox (SB A), enter a walkway, open a blue plastic box (bB) as opposed to red and yellow box (rB/yB), and return to SB A. The boxes' position was changed clockwise in subsequent runs. During testing 1, time to leave SB A and open bB, and time to leave bB and return to SB A was recorded and a score was given based on attempts to open and/or investigate bB and/or rB and yB. During testing 2, yB had to be opened instead of bB and yB (intradimensional shift). Each pig completes training, testing 1 and testing 2 biannually. Results/outcome: The animals show a good tolerance of the method. Cross sectional and longitudinal data analysis is in progress using SPSS 22.0. Conclusion: The data collected to date shows that implementation of the "Discrimination Test" is feasible and well tolerated. It is hypothesised that performance of the test is impaired in tgHD minipigs compared to controls. We expect to report first between group comparisons at the meeting. Acknowledgement: This study was funded by the CHDI foundation.